Changes in liver and spleen volumes after living liver donation: A report from the adult‐to‐adult living donor liver transplantation cohort study (A2ALL). Issue 2 (February 2015) - Emond, Jean C.; Fisher, Robert A.; Everson, Gregory; Samstein, Benjamin; Pomposelli, James J.; Zhao, Binsheng; Forney, Sarah; Olthoff, Kim M.; Baker, Talia B.; Gillespie, Brenda W.; Merion, Robert M.
<x xml:space="preserve">Abstract</x> Previous reports have drawn attention to persistently decreased platelet counts among liver donors. We hypothesized an etiologic association between altered platelet counts and postdonation splenomegaly and sought to explore this relationship. This study analyzed de‐identified computed tomography/magnetic resonance scans of 388 donors from 9 Adult‐to‐Adult Living Donor Liver Transplantation Cohort Study centers read at a central computational image analysis laboratory. Resulting liver and spleen volumes were correlated with time‐matched clinical laboratory values. Predonation liver volumes varied 2‐fold in healthy subjects, even when they were normalized by the body surface area (BSA; range = 522‐1887 cc/m2, n = 346). At month 3 (M3), postdonation liver volumes were, on average, 79% of predonation volumes [interquartile range (IQR) = 73%‐86%, n = 165] and approached 88% at year 1 (Y1; IQR = 80%‐93%, n = 75). The mean spleen volume before donation was 245 cc (n = 346). Spleen volumes greater than 100% of the predonation volume occurred in 92% of donors at M3 (n = 165) and in 88% at Y1 after donation (n = 75). We sought to develop a standard spleen volume (SSV) model to predict normal spleen volumes in donors before donation and found that decreased platelet counts, a younger age, a higher predonation liver volume, higher hemoglobin levels, and a higher BSA predicted a larger spleen volume (n = 344, R2 = 0.52). When this was applied to postdonation values, some large volumes were underpredicted by the SSV model. Models developed on the basis of the reduced sample of postdonation volumes yielded smaller underpredictions. These findings confirm previous observations of thrombocytopenia being associated with splenomegaly after donation. The results of the SSV model suggest that the biology of this phenomenon is complex. This merits further long‐term mechanistic studies of liver donors with an investigation of the role of other factors such as thrombopoietin and exposure to viral infections to better understand the evolution of the spleen volume after liver donation. Liver Transpl 21:151‐161, 2015. © 2014 AASLD.